Eficácia do glyphosate no controle de macrófitas em condição de casa de vegetação - Cruz, C. [UNESP]; Silva, A. F. [UNESP]; Luna, L. V. [UNESP]; Yamauchi, A. K.F. [UNESP]; Garlich, N. [UNESP]; Pitelli, R. A. [UNESP] (My University, 2015)
The aim of this study was to assess the effectiveness of glyphosate, as Rodeo® formulation, to control Eichhornia crassipes, Pistia stratiotes, Salvinia molesta, Salvinia herzogii and Urochloa subquadripara, under greenhouse conditions. The doses assessed were (480, 960, 1440, 1920, 2400, 2880, 3360 and 3840 g ha-1 of glyphosate) with 0.5% of the Aterbane® BR surfactant and a control, with no herbicide application. All experiments were conducted in a completely randomized experimental design with ten replications. Applications were carried out by precision backpack sprayer at a CO2 constant pressure of 25 psi and spray solution consumption of 200 L ha-1. Product effectiveness was determined by assessing the growth inhibitions and phytotoxicity signals during the periods of 3, 7, 15, 21, 30 and 45 days after application (DAA). At 45 DAA, the highest glyphosate dose (3840 g ha-1) displayed 100% effectiveness for all four macrophyte species. Under greenhouse conditions, the glyphosate in formulation Rodeo® with 0.5% of Aterbarne® BR surfactant showed excellent effectiveness, inhibiting the growth of the floating aquatic macrophytes. This procedure can be included on the tillage plans for these species.
Glyphosate effectiveness in the control of macrophytes under a greenhouse condition
Keywords: Salvinia and tanner-grass; Water hyacinth; Water lettuce